ANALISIS ANTRIAN PASIEN RAWAT INAP BERDASARKAN SPESIALISASI PENYAKIT DI RSUP Dr KARIADI SEMARANG - Rahayu, Anisa Alfiani; Sugito, Sugito; Sudarno, Sudarno (Department of Statistics, Faculty of Science and Mathematics, Universitas Diponegoro, 2013)
The arrival rate of inpatients at the Dr Kariadi Hospital very much in every day, either derived from poly outpatient and the ER (emergency room). With limited bed capacity, the hospital often refer patients to the hospital inpatient others who still have bed capacity. But many patients who do not want to refer to others hospitals and they will waiting for a inpatient ward. Therefore, it is necessary to determine the queuing system model according to the conditions and characteristics of the queue service facilities in Dr Kariadi hospital based specialization disease patients. Based on the analysis of data obtained for each specialization disease models queuing system that occurs in hospital based specialties Dr Kariadi hospital disease is (M / M / c): (GD / ∞ / ∞) and the model of the queue at the payment system is (M / M / 4): (GD / ∞ / ∞). Number of inpatient services by specialist have been effective because of the amount of each disease have many specialists. As for the payment / checkout number of officers who perform duties detailed breakdown of costs need to be added so that patients who come do not wait too long to get service.